Two Pass Weed Control Programs in Conventional Tillage Xtend Soybeans - D. E. Peterson; C. Thompson; C. L. Minihan (Kansas Agricultural Experiment Station Research Reports, 2017)
The development of glyphosate-resistant weeds has greatly complicated weed control in soybeans. Roundup Ready 2 Xtend (dicamba tolerant) soybeans provide growers an alternative herbicide option for postemergence weed control in conventional tillage soybeans. Two pass programs consisting of preemergence residual herbicides followed by postemergence Roundup Power Max plus dicamba provided excellent weed control, superior to a single postemergence treatment with Roundup Power Max plus dicamba.
Keywords: Roundup Ready 2 Xtend soybeans; Palmer amaranth; velvetleaf; ivyleaf morningglory